2012
DOI: 10.5007/2175-8077.2012v14n32p35
|View full text |Cite
|
Sign up to set email alerts
|

Executivos brasileiros: na contramão do perfil deificado da liderança transformacional

Abstract: O objetivo deste artigo é relacionar o tipo psicológico dos executivos que atuam no nível estratégico das grandes empresas com as características que a literatura aponta para o líder transformacional que, embora deificado, é o mais citado pela literatura atual. O referencial teórico apresenta uma síntese da literatura sobre liderança, desde a Teoria dos traços até a Teoria da liderança transformacional. Utiliza-se a ferramenta MBTI (Myers-BriggsTypeIndicator), um indicador de tipos psicológicos baseado no trab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
3
0
3
Order By: Relevance
“…This may explain why Brazilians in leading roles are not likely to display transformational behaviors in dealing with their subordinates (c.f. Carvalho, 2010;Carvalho et al, 2012). Nevertheless, as observed by researchers involved in the GLOBE study, participants from Latin American countries such as Brazil ranked high on their endorsement of leadership dimensions such as charismatic/value based leadership, i.e.…”
Section: Formal Performancementioning
confidence: 98%
See 1 more Smart Citation
“…This may explain why Brazilians in leading roles are not likely to display transformational behaviors in dealing with their subordinates (c.f. Carvalho, 2010;Carvalho et al, 2012). Nevertheless, as observed by researchers involved in the GLOBE study, participants from Latin American countries such as Brazil ranked high on their endorsement of leadership dimensions such as charismatic/value based leadership, i.e.…”
Section: Formal Performancementioning
confidence: 98%
“…Although some research on transformational leadership can be found in the local management literature (e.g. Carvalho, Tanure, Santos, & Lima, 2012;Marchiori, Vilaça, Simões, Pinto, & Fonseca, 2010), quantitative field studies inspecting the connections between transformational leadership behaviors and follower performance are still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Existem, também, abordagens mais recentes sobre liderança (Carvalho, Tanure, Santos, & Lima, 2012;Dionne et al, 2014;Esper & Cunha, 2015). Trata-se das abordagens cultural, visionária, autêntica, carismática, ética e a dicotomia transformacional -transacional, além da incorporação de outras teorias vindas da psicologia.…”
Section: Liderança: Conceitos E Modelosunclassified
“…A abordagem comportamental originou-se no início dos anos 1950, baseandose na ideia de que o indivíduo era capaz de aprender e desenvolver características para se tornar um líder (BLAKE; MOU-TON, 1978;LIMA, 2011;TANURE;SAN-TOS et al, 2012). A presença do liderado também pode ser considerada um salto nesta teoria, já que ele, mesmo que de maneira discreta, passou a ser citado como um objeto influenciador do líder, oferecendo bases para a tentativa de se relacionar a percepção do líder e do liderado quanto ao estilo de liderança LIMA, 2011;TANURE;SANTOS et al, 2012).…”
Section: Referencial Teórico a Abordagem Comportamental E A Teoria Dounclassified